Pengaruh Kualitas Layanan Aplikasi Dana terhadap Kepuasan Pelanggan dalam Melakukan Transaksi Secara Online sebagai Alat Pembayaran Elektronik (E-Payment) - Afidah Hissi Heryanti (Journal on Education, 2023)
DANA is an application that provides convenience in digital transactions. In Indonesia, payment aplications that can facilitate consumer transactions continue to develop, including OVO, Go-pay, LinkAja, DANA, I.saku and DOKU, from several payment applications that will be studied by researchers, namely the DANA application. Currenlty, the DANA application is an online tool as well as fintech which is well known throughout Indonesia. Thereore, the DANA application is a stage for developing an online payment system so that it will be better in the future. So, this study carried out the stages of data collection and data analysis. Data collection was carried out by distributing questionaires that had been filled in by the respondents. The samples taken in study were 30 people. The results of the study show that customer satisfaction has a positive effect on the service quality of the DANA feature from the independent variable, which means that customer satisfaction in the DANA application can be influenced by service quality. The software used in this study uses SPSS Version 16.0